Efektivitas Ekstrak Kayu Secang sebagai Agen Curing Alami pada Mutu Daging Sapi Knuckle - Tanty Sulistiani Widodo; Lina Herlinawati (Ma'soem University, 2026)
The knuckle is the hind leg portion of beef, often also referred to as coconut meat. This meat contains a complete range of nutrients, making it an ideal medium for microbial growth. Curing is a method of preserving meat by adding table salt as well as nitrate or nitrite salts to achieve a stable red color and distinctive flavor. However, the use of nitrite carries risks, as it can act as a precursor for the formation of nitrosamines, which are carcinogenic through their reaction with amine compounds. This situation highlights the need to develop safer alternative materials for the curing process. One promising alternative is sappan wood, which contains the red pigment brazilein, whose color characteristics are influenced by pH. The concentration of sappan wood extract has a positive and significant effect on antimicrobial activity, both in liquid and powdered forms. This study aims to compare the effectiveness of three types of sappan wood extract on the physical, microbiological, and sensory responses of meat, as well as to determine the best treatment based on these responses. The study employed a Completely Randomized Design (CRD) with one factor: the type of sappan wood extract, which consisted of three levels (liquid extract, powdered extract, and extract solution). Each treatment was repeated six times, resulting in a total of 18 experimental units. Observations included Total Plate Count (TPC), color difference, and sensory evaluation using a scoring method for color, aroma, and texture (handfeel) conducted by 10 selected panelists. The results showed that the best curing process was achieved using the sappan wood extract solution. The analysis of knuckle beef cured with the extract solution revealed a TPC of 913 cfu/mL, a color difference (?E) of 8.60, a color score of 4.03, an aroma score of 3.20, and a texture score of 3.67.